An azabenz-annulated perylenediimide with tetraphenylethene units: Aggregation-induced emission, mechanochromic fluorescence, and cell imaging. (April 2022) - Sun, Hua; Jin, Jiale; Wang, Qi; Wang, Shifan; Na, Weidan; Li, Zhao; Yao, Bing; Sun, Po; Dong, Liming; Hang, Xiao-Chun
Abstract: Organic materials with strong solid-state fluorescence and sensitive stimuli responsiveness are highly desired for both fundamental research and practical applications. We report herein an azabenz-annulated perylenediimide (AzaBPDI)-based dye, AzaBP-TPE, which contains tetraphenylethene units in the planar aromatic structure. AzaBP-TPE undergoes typical intramolecular charge transfer, aggregation-induced emission, and mechanochromic fluorescence. In the solid state, AzaBP-TPE emits bright-yellow light with a photoluminescence quantum yield of 27%, and this emission becomes red fluorescence when MCF is induced, by using mechanical force to collapse the crystalline structure. Moreover, bright-yellow fluorescence can be recovered by exposing AzaBP-TPE powder to chloroform vapor. Notably, AzaBP-TPE nanoparticles can penetrate live cells and emit red light and, therefore, can be applied as a functional dye in bio-imaging. Graphical abstract: Image 1 Highlights: A novel azabenz-annulated perylenediimide-based dye, AzaBP-TPE was developed. AzaBP-TPE exhibits typical AIE and reversible MCF in the solid state. Good biocompatibility indicates AzaBP-TPE a potential functional dye for cell-imaging.